Uji Efektivitas Pemanfaatan Serbuk Biji Kelor Sebagai Alternatif Koagulan Dalam Menurunkan COD, BOD dan TSS Pada Air Limbah Laundry - Rozan Thabrani; Didin Agustian Permadi (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Inorganic coagulants are widely used in wastewater treatment. However, long-term negative effects have led to their replacement by organic coagulants derived from natural sources or environmentally friendly biocoagulants. In Indonesia, there are many plants that can be used as biocoagulants, one of which is the seeds of Moringa oleifera (Moringa oleifera). This research aims to analyse the influence of Moringa oleifera seed powder on COD, BOD and TSS parameters in laundry wastewater using the glass test method. The research variables include variations in doses of Moringa oleifera seed powder (0.8 g; 1.0 g; 1.5 g; 2 g; and 3 g). The study is analysed by comparing with standard limits and calculating the percentage removal of each test parameter. The results indicate that the different doses of Moringa oleifera seed powder can affect the levels of COD, BOD and TSS in wastewater. The optimum dose for reducing COD and TSS is 1.5 grams with a reduction percentage of 84% for COD and 94% for TSS. For BOD, the optimum dose is 1 gram with a reduction of 85%.